Making a Dent in Dent Disease. Issue 2 (11th September 2020) - Shipman, Katherine E; Weisz, Ora A
Abstract: Dent disease (DD) is a rare kidney disorder caused by mutations in the Cl − /H + exchanger ClC-5. Extensive physiologic characterization of the transporter has begun to illuminate its role in endosomal ion homeostasis. Nevertheless, we have yet to understand how loss of ClC-5 function in the kidney proximal tubule impairs membrane traffic of megalin and cubilin receptors to cause the low molecular weight proteinuria characteristic of DD. This review identifies open questions that remain to be answered, evaluates the current literature addressing these questions, and suggests new testable models that may link loss of ClC-5 function to tubular proteinuria in DD.